AN ANALYSIS OF STUDENTS’ GRAMMATICAL ERRORS IN WRITING REPORT TEXT AT ELEVENTH GRADE SMAS TAMANSISWA SINGOSARI MEDAN - Pakpahan, Aulia Fatin (Faculty of Tarbiyah nad Teacher Training, 2024)
This study, titled “An Analysis of Students’ Grammatical Errors in Writing Report Text at Eleventh Grade SMAS Tamansiswa Singosari Medan”. The study aimed to find out what types of grammatical errors in the students' report text writing and the causes of the errors. The research employed a descriptive qualitative method, focusing on 11th-grade students from the IPS2 class at SMAS Tamansiswa Singosari Medan. Data collection was conducted through documentation and interviews. The analysis followed the steps outlined by Gass and Selinker, which included collecting the data, identifying students’ errors, classifying errors, and analyzing cause of error. The findings revealed four types of errors in the students' report texts: omission, addition, misformation, and misordering, totaling 44 errors. Specifically, there were 10 omission errors (22.72%), 13 addition errors (29.54%), 12 misformation errors (27.27%), and 9 misordering errors (20.45%). The most frequent error type was addition, with the total 13 or 29.54% errors. The causes of these errors were identified as carelessness, influence from the first language, and issues with translation.